An Assessment of Ambient and Heated Forced Air Drying Pre-treatments for Enhancing the Quality of Various Forest Biomass Feedstocks - Mak, Jay; Landry, Hubert; Grieger, Lorne; Agnew, Joy; Krigstin, Sally; Helmeste, Christopher; Wetzel, Suzanne; Madrali, Sebnem; Volpé, Sylvain (Frontiers in Energy Research, 2020)
Maintaining high quality feedstock storage for sustained bioenergy production continues to be a challenge within the supply chain. Though forestry by-products have the potential to provide a carbon-neutral energy source that can be both economic and environmentally friendly, the heterogeneous nature of woody biomass makes the material challenging to store for long periods of time without material degradation, freezing, and fire concerns if not managed properly. The following study evaluated the scalable use of natural air drying (NAD) with and without supplemental heat on multiple woody biomass feedstocks (hog fuel, sawmill chips, and bark) to determine drying rates and feasibility in Western Canada. Test results demonstrated that NAD has the potential to dry and condition multiple types of woody biomass, while providing a positive net energy gain of 9-32% compared to the original biomass energy content. The use of supplemental heat resulted in an energy gain of 3 to -13% due to the increased heating energy consumption, but may be applicable in some circumstances when faster drying is required, weather conditions are unfavorable and/or alternative low-cost heating sources are available. Therefore, NAD shows promise in providing an alternative low-cost drying option for enhancing woody biomass feedstock in storage.